GRAVITY ANOMALIES, THE DEEP STRUCTURE, AND DYNAMIC PROCESSES BENEATH THE TIEN SHAN - Burov E.V.; Kogan M.G.; Lyon-Caen H.; Molnar P. (My University, 1990)
Bouguer gravity anomalies over the Tien Shan and Pamir are large and negative, and therefore consistent with crustal thickening beneath both mountain ranges. Gravity anomalies over the western Tien Shan are within about 10 mgal of those expected for local Airy isostatic equilibrium, but those over the eastern Tien Shan are up to 50 mgal too large and negative. Thus they require static or dynamic support of an uncompensated mass deficit. These gravity anomalies cannot be matched using regional compensation of the weight of the range on a continuous elastic plate. A simple model of two separate elastic plates extending north and south from the axis of the Tien Shan can allow an adequate fit of observed and calculated anomalies. The flexural rigidity of the northern plate must be quite small (D < 1023 N m, corresponding to an equivalent effective elastic thicknessTE < 25 km), but that of the southern plate must be larger (D ≈ 1024 N m, TE ≈ 50–60 km). The data for the eastern Tien Shan cannot be fit without a force per unit length of roughly 1–4 × 1012 N, or by a bending moment, applied to the end of the southern plate. Thus either a deep mass per unit length of about 1–4 × 1011 kg/m must underlie the eastern part of the range, or dynamic (deviatoric tensional) normal stresses of up to about 5 MPa, due to flow in the asthenosphere, must pull the Tien Shan down. Probably a combination of them, resulting from the formation and sinking of a thickened lithospheric root, causes the deflection of the Moho and the deviations from local isostatic equilibrium.